Alberta's Rural Physician Action Plan: an integrated approach to education, recruitment and retention - Wilson, D R (1998)
This paper describes the development and characteristics of a comprehensive, integrated and sustained program for the education, recruitment and retention of physicians for rural practice in Alberta--the Rural Physician Action Plan. The participation of key stakeholders (including government, the provincial medical association, the licensing authority, faculties of medicine, practising rural physicians and regional health authorities) and a sustained program budget have been key organizational issues for success. Critical to the effectiveness of this program has been the focus on professional and lifestyle issues targeting 3 distinct groups: physicians in training, physicians in practice, and rural communities and health authorities. Substantial program funding since 1991-92 of up to $3 million per year has increased rural-based activities significantly. For example, 87% of medical students and 91% of residents in family medicine in Alberta now experience 4 weeks or more of rural practice. The authors believe that the historic issues and recent trends militating against recruitment and retention of rural physicians will continue unchecked without comprehensive and sustained approaches such as Alberta's Rural Physician Action Plan.